Food and Drug Monitoring Agency (BPOM) in Protection Consumer To Product Maintenance Skin - Meldasari, Tritami; Khalid, Hasbuddin; Tjolleng, Arfah (Faculty of Law, Universitas Muslim Indonesia, 2025)
This study aims to determine and analyze the role of the BPOM (Indonesian National Agency of Drug and Food Control) in protecting consumers from skincare products containing mercury. It also aims to identify and analyze the legal actions taken by BPOM Makassar City against skincare products that do not meet quality standards. This research uses an empirical legal research method, which involves field data as the primary source, such as interviews and observations. The results of the study indicate: (1) The role of BPOM in providing consumer protection against the circulation of skincare products containing mercury by monitoring and supervising the circulation of skincare products in the market to ensure they do not contain harmful substances, implementing pre-market surveillance, conducting post-market surveillance, and inspecting skincare products circulating in the market. (2) The legal actions taken by BPOM against skincare products that do not meet quality standards include administrative sanctions and criminal sanctions. As recommendations: (1) The government needs to implement stricter supervision to better protect consumers from the use of cosmetics that do not have BPOM circulation permits. (2) There must be good cooperation between the government, BPOM, and law enforcement authorities in efforts to protect consumers from the circulation of cosmetics that do not meet the standards, through regular supervision of producers and business actors, as well as providing outreach to the public to raise awareness.